The Effect of Profitability and Transfer Pricing on Tax Avoidance in LQ45 Companies Listed on The IDX For The 2021-2024 Period - Amani, Fathiya; Masruri, Fahrul Alam; Krisdina, Tiana Fenny (Journal of Business, Accounting and Finance, 2025)
This study aims to analyze the effect of profitability and transfer pricing on tax avoidance in LQ45 companies listed on the IDX for the 2021-2024 period. The independent variables in this study are profitability and transfer pricing. While the dependent variable in this study is tax avoidance. The population and sample in this study are companies listed on the LQ45 index listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. The sampling method used is purposive sampling, according to the predetermined criteria, a sample of 12 companies was obtained and a total of 48 financial report sample data. The analysis techniques used are descriptive analysis tests, classical assumption tests, hypothesis tests, namely multiple linear regression analysis tests, correlation coefficient tests, determination coefficient tests, t tests and F tests. This study is a quantitative study where data is processed using the SPSS version 26 application. The results of this study indicate that partially profitability has a significant negative effect on tax avoidance and transfer pricing does not affect tax avoidance. In addition, profitability and transfer pricing do not simultaneously affect tax avoidance.